A tale of the broken heart: peripartum cardiomyopathy, a case report (Faculty of Medicine Universitas Indonesia, 2016)
Progressive dyspnea following childbirth warrants a prompt suspicion into the diagnosis of peripartum cardiomyopathy, PPCM. Pump failure causes an inadequate cardiac output which ultimately contributes to PPCM high mortality rate; however early airway control, vigilant fluid balance and vasoactive support will substantially reduce the incidence of patients falling into decompensated heart failure. More importantly, it is imperative that these patients are cared in a setting where continuous hemodynamic monitoring is available. This case report serves as a reminder not to focus end-point therapy solely on blood pressure readings, but to observe signs and symptoms of hypoperfusion such as cold clammy skin, cool extremities, decreased urine output and mental status.